Swear Words as Speech Event: Discourse Patterns and Functions Among EFL Context - Agis Andriani; Verain Aulia Rahma; Dewi Rosmala (RETORIKA: Jurnal Ilmu Bahasa, 2026)
This study examines the increasing significance of pragmatic competence in English as a Foreign Language (EFL) settings, specifically with the comprehension of socially sensitive language, including swearing words. Despite their common use in daily interactions to convey emotion, solidarity, and identity, swear words are not frequently examined in EFL research and are typically dismissed as just unacceptable or inappropriate language rather than valuable communicative tools. In Indonesia, swearing reflects the tension between global linguistic influences and local cultural norms, highlighting its connection to politeness and moral identity. This study aims to analyze the patterns and functions of sweari    ng used by EFL students in university interactions and to explore how this language reflects wider social and communicative processes. A descriptive qualitative technique using an exploratory case study design was used to gather data from 22 students of the 2022 English Department at the University of Siliwangi through open-ended questionnaires, supported with public comments from YouTube and X. According to Hymes' ethnography of communication, known as the SPEAKING model, the results indicate two predominant forms of swearing: abusive and expletive. Swearing serves not just as a form of verbal abuse but also as an expressive and interactional approach to foster solidarity, indicate closeness, and articulate dissatisfaction in contextually suitable ways. The findings emphasize EFL learners as proactive constructors of meaning who navigate identity and social relationships through language, highlighting the significance of cultural sensitivity, contextual awareness, and pragmatic competence in managing multifaceted language practices in intercultural communication.